Are Overconfident CEOs Born or Made? Evidence of Self-Attribution Bias from Frequent Acquirers - Billett, Matthew T.; Qian, Yiming (Management Science, 2008)
We explore the history of mergers and acquisitions made by individual CEOs. Our study has three main findings: (1) CEOs' first deals exhibit zero announcement effects while their subsequent deals exhibit negative announcement effects; (2) while acquisition likelihood increases in the performance associated with previous acquisitions, previous positive performance does not curb the negative wealth effects associated with subsequent deals; and (3) CEOs' net purchase of stock is greater preceding subsequent deals than it is for first deals. We interpret these results as consistent with self-attribution bias leading to overconfidence. We also find evidence that the market anticipates future deals based on the CEO's acquisition history and impounds such anticipation into stock prices.